The use of verbal inflections in Inuktitut child and child-directed speech - Lee, Hannah; Johnson, Olga Alice; Allen, Shanley E. M. (Journal of Monolingual and Bilingual Speech, 2023)
Inuktitut is a polysynthetic agglutinative language of the Inuit-Yupik-Unangan language family, with nearly 900 verbal inflections. Despite the complexity of its inflectional system, children acquiring Inuktitut as their native language start using inflections relatively early (Crago & Allen, 2001; Swift & Allen, 2002). One hypothesis is that caregivers simplify their child-directed speech (CDS) in a way that helps the children to break into the system. To date, relatively little research has focused on the use of inflections in CDS. The current study uses the data from eight Inuktitut-speaking children aged 1-4 years and their mothers to investigate whether and how the use of verbal inflections (VIs) in CDS changes as the children advance linguistically, and whether the children’s use of VI corresponds with the input they receive. We found a significant increase in the number of different VIs and the total number of VIs in the mothers’ CDS as their children went from Stage 1 to Stage 6 of linguistic development. Children’s use of VIs follows the general patterns of VI acquisition cross-linguistically. Further, as children progressed linguistically, they seemed to rely less on the input from their mothers, since they increasingly used VIs not previously found in their mothers’ CDS (from 16% in Stage 2 to 75% in Stage 6). These results correspond with other studies’ findings of CDS simplification and extend our understanding of how inflectional morphology is adapted in CDS.